Implementation Of Independent Of Learning For Accounting Students - Fitriani Fitriani; Ririn Apriana (Universitas 17 Agustus 1945 Semarang, 2023)
Because they aid in the understanding of the actual world by students, internships are an essential component of curricula in higher education. The Independent Campus Learning Internship program, which was introduced by the Republic of Indonesia's Ministry of Education, Culture, Research, and Technology at the beginning of 2020, is the subject of this study. The purpose of this program is to expose students to the outside world. experience working in an environment relevant to their subject of study in order to enhance graduates' hard and soft skills. Thus, the purpose of this study is to determine what competencies accounting students pick up from their MBKM internships across a range of sectors. In order to collect data for this study, accounting students in Indonesia who are doing MBKM internships are sent Google forms over social media. Using descriptive statistical methods, the data was analyzed, and 87 out of the 98 respondents made up a viable sample size. The analysis's findings demonstrated that most students had made progress in the hard and soft abilities needed in the job. The majority of students concur that their confidence in working in accounting has grown as a result of their internships, which have also enabled them to work independently on tasks, cooperate with others, evaluate data, and solve problems on their own. The majority of interns who complete their internships receive employment offers, demonstrating the effectiveness of internship programs in enhancing the abilities that businesses and industry deman.